The effects of morinda citrifolia, momordica charantia and centella asiatica extracts on lipoprotein lipase and 3T3-L1 preadipocytes. - Sahib, Najla Gooda; Abdul Hamid, Azizah; Kitts, David; Purnama, Monica; Saari, Nazamid; Abas, Faridah (Wiley-Blackwell, 2011)
The effect of Morinda citrifolia fruit (MCFE), Momordica charantia (MCE) and Centella asiatica (CAE) extracts on lipoprotein lipase (LPL) activity, proliferation and differentiation of 3T3-L1 preadipocytes was investigated. The inhibitory effect of the extracts on LPL activity was determined in vitro. The extent of cell proliferation was determined utilizing 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and the degree of differentiation was measured by Oil Red O staining assay. Extracts were analyzed for total phenolic compounds and flavonoids utilizing Folin-Ciocalteu assay and high-performance liquid chromatography, respectively. Results showed that, at 1mg/mL, MCFE demonstrated the highest inhibitory effect (21.4±2.3%), compared to the other extracts tested. On the other hand, MCE demonstrated the highest inhibitory effect on both proliferation and differentiation of preadipocytes (LC 50of 1.6mg/L). LC 50 refers to the concentration of extracts (mg/mL) to cause a 50% reduction in viable cells. Results also revealed that all extracts consisted of high concentration of phenolic compounds, with catechin and epicatechin predominantly present in all three extracts, that maybe responsible for the activities measured.